Hedonic Test Of Lipstick Combination Of Red Dragon Fruit Peel Extract (Hylocereus Polyrhizus) And Beetroot Tuber Extract (Beta Vulgaris L.) As Natural Colorant - Fauzia, Rizki Rahmah; Karsidin, Bambang; Tristianti, Deswita (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Not all waste from natural materials produced can be utilized properly by humans to produce higher economic value. The waste in question is red dragon fruit skin which contains anthocyanin pigments and betasianin pigments. Pigments can be used as colorants in lipstick but the intensity of the resulting color is less attractive. This study aims to determine the lipstick combination of Red Dragon fruit peel extract (Hylocereus polyrhizus) and Beet tuber extract (Beta vulgaris L.) most preferred by panelists as a natural colorant. The method used in this study was experimental. Preparation of Red Dragon fruit peel extract and Beetroot tuber extract using maceration method with 70% ethanol solvent. Then the extract was made into 3 lipstick preparation formulas at a concentration of 30% with a ratio of 1: 2 (X1), 1,5 : 1.5 (X2) and 2: 1 (X3). Hedonic tests include texture, color, aroma and appearance of lipstick preparations using a Likert scale. The combination lipstick produces color and percentage of liking, namely purple and preferred by 43.75% (X1), pink with 51.25% hedonic percentage (X2), and the most preferred by 58.75% (X3) with a dark red color, while the negative control has a yellow color with the smallest liking value of 28.75%.